Pre-sensitization of Malignant B Cells through Venetoclax significantly improves the cytotoxic efficacy of CD19.CAR-T Cells - Yang, Mingya; Wang, Lei; Neuber, Brigitte; Wang, Sanmei; Sauer, Tim; Sellner, Leopold; Schubert, Maria-Luisa; Hückelhoven-Krauss, Angela; Kleist, Christian; Eckstein, Volker; Müller-Tidow, Carsten; Dreger, Peter; et al. (Frontiers in immunology, 2020)
Chimeric antigen receptor (CAR) T cell therapy has shown promising responses in patients with refractory or relapsed aggressive B-cell malignancies that are resistant to conventional chemotherapy or stem cell transplantation. A potentially combinatorial therapeutic strategy may be the inhibition of anti-apoptotic Bcl-2 family proteins, overexpressed in most cancer cells. In this study we investigated the combination of 3rd generation CD19.CAR-T cells and the BH3 mimetics venetoclax, a Bcl-2 inhibitor, and S63845, a Mcl-1 inhibitor, under three different treatment conditions: pre-sensitization of cancer cells with BH3 mimetics followed by CAR-T cell treatment, simultaneous combination therapy, and the administration of BH3 mimetics after CAR-T cell treatment. Our results showed that administration of CAR-T cells and BH3 mimetics had a significant effect on the quantity and quality of CD19.CAR-T cells. The administration of BH3 mimetics prior to CAR-T cell therapy exerted an enhanced cytotoxic efficacy by upregulating the CD19 expression and pro-apoptotic proteins in highly sensitive tumor cells, and thereby improving both CD19.CAR-T cell cytotoxicity and persistence. In simultaneous and post-treatment approaches, however, the quantity of CAR-T cells was adversely affected. Our findings indicate pre-sensitization of highly sensitive tumor cells with BH3 mimetics could enhance the cytotoxic efficacy of CAR-T cell treatment.